High temperature Raman spectroscopic analysis of the crystal growth of Bi2ZnOB2O6 - Zhang, Ji; Liu, Daojun (Canadian journal of chemistry, 2024)
Micromechanism of crystal growth has received considerable attention as a fundamental subject. However, in situ observation of the crystal growth process remains challenging. In this study, high-temperature Raman spectroscopy has been utilized to investigate the growth pattern of Bi2ZnOB2O6 crystals via in situ exploration of the starting solution structure near the crystal–solution interface. The experimental results show that the solution primarily consists of ZO4 and BO3 units corresponding to 370, 539, 664, and 1293 cm−1 vibration frequencies. These units connect with each other forming longer chains in the area close to the crystal, and they are related to the presence of low-wavenumber vibrations in the Raman spectrum. Furthermore, a loose embryonic structure of the Bi2ZnOB2O6 crystal is observed near the crystal–solution interface owing to the formation of Bi–O bonds. Therefore, this study successfully provides a clear understanding of the formation mechanism of Bi2ZnOB2O6 crystals.